2021
DOI: 10.1016/j.pedn.2021.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual Needs of Brazilian Children and Adolescents with Chronic Illnesses: A Thematic Analysis

Abstract: To identify the spiritual needs of children and adolescents with chronic illnesses and how these needs are met by health professionals during hospitalization. Design and methods: A qualitative descriptive study was developed with 35 children and adolescents, between 7 and 18 years old, diagnosed with cancer, cystic fibrosis, and type 1 diabetes. Interviews with photo-elicitation were conducted during the hospitalization at a Brazilian public pediatric hospital. Findings were treated using thematic analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
10
0
2
Order By: Relevance
“…Alvarenga and colleagues [ 43 ], in their exploration of the spiritual needs of children and adolescents with cancer, cystic fibrosis, and type 1 diabetes mellitus, by means of interviews with photo-elicitation, found that believing in a benevolent God gave pediatric patients hope and helped them to integrate the meaning of their disease. Encouragement and comfort were also gained from members of their religious communities.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Alvarenga and colleagues [ 43 ], in their exploration of the spiritual needs of children and adolescents with cancer, cystic fibrosis, and type 1 diabetes mellitus, by means of interviews with photo-elicitation, found that believing in a benevolent God gave pediatric patients hope and helped them to integrate the meaning of their disease. Encouragement and comfort were also gained from members of their religious communities.…”
Section: Resultsmentioning
confidence: 99%
“…Thirdly, beyond personal and individual experiences of religiosity and spirituality, some works in this scoping review highlighted that religious communities [ 43 , 58 ] and spiritual anchors (e.g., parents; [ 60 ]) played a relevant role in the lives of adolescents struggling with a chronic illness, as they supported them spiritually and emotionally and gave them the strength to fight against their condition. Thus, these findings echoed those theoretical arguments and the empirical evidence revealing that religiosity and spirituality provide adolescents with social contexts where they might come into contact with sources of inspiration and webs of support, as well as have trustworthy relationships that favor their healthy development [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have described its relationship with patient reported health outcomes, especially in the areas of oncology and mental health ( Koenig, 2012 ; McLouth et al, 2021 ). Adolescents with life-threatening diseases or severe chronic conditions meet challenges in coping with their condition and spirituality may affect the psychological and behavioral adjustment ( Damsma Bakker et al, 2018 ; Alvarenga et al, 2021 ). The role of spiritual wellbeing, however, is not well understood in young people, and the number of reliable and valid instruments to assess the construct in this age group is still limited ( Cotton et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%